Comparison of The Performance of Civil Employee Teachers with Honorers at SMK Negeri 3 Sinjai - Aris Baharuddin; Dewi Sulfa Saguni; Risma Niswaty; Herling Herling (Universitas Negeri Makassar, 2021)
This study aims to determine the comparison of the performance of civil servant teachers with honorer at SMK Negeri 3 Sinjai. Data collection techniques used are through observation, questionnaires (questionnaire) and documentation. The data that has been obtained from the research results are processed using data analysis techniques consisting of descriptive analysis techniques and inferential statistical analysis. The results show that based on the indicators used in each variable, these results indicate that the performance of civil servant teachers is in the very good category, for the performance of honorary teachers is in the very good category at SMK Negeri 3 Sinjai. While a significant difference between the performance of civil servant teachers with honorary results, it appears that the probability value is greater than the value is significant, thus the result is that there is no significant difference between the performance of civil servant teachers and honorary teachers at SMK Negeri 3 Sinjai.